Current and Emerging Protocols for Carbon Measurement in Agricultural Soils - Suraj Melkani; Noel Manirakiza; Shirley M. Baker; Jehangir H. Bhadha (EDIS)
Soils have the capacity to function as a sink of atmospheric carbon dioxide and are crucial for climate regulation. Soils have the potential to store around 1.5 to 2.4 trillion metric tons of carbon (C) in the soil globally. They contain large C pools that can store three times more C than the atmosphere and four times more than plants. These massive C sinks have the potential to reverse soil degradation, mitigate climate change, and enhance food security. It is therefore essential to monitor the C cycle by accurately measuring the amount of soil C in agricultural fields. This can help in developing sustainable management practices that can minimize C emissions and sequester C into the soil from the atmosphere. This publication describes the various current and emerging protocols that can be used to measure soil C.